2019
DOI: 10.15761/npc.1000201
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the dietary consumption of patients with probable dementia of Alzheimer type, at different stages: Observational study in a public outpatient clinic in são paulo, Brazil

Abstract: Purpose: to verify the correlation of the ingested diet with the nutritional status of Alzheimer disease (AD) patients; observation of fiber and fluid consumption and intestinal function.Methods: Cross-sectional study with 77 patients of both genders and their caregivers who were referred to nutritional status care in the three phases (CDR) of the AD. All answered the food anamnesis where it was possible to establish the amount of calories, macronutrients and micronutrients. Anthropometric measurements of weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…However, this information was not included in the pooled analysis because data regarding the standard deviation was not available [ 20 ]. Another study from Brazil made by De Andrade Vieira et al found that the total energy in AD patients was 1715.3±492.3 kcal [ 21 ]. Medeiros et al also reported a total energy consumption of 1238.44 kcal among AD patients living in home health care centers [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this information was not included in the pooled analysis because data regarding the standard deviation was not available [ 20 ]. Another study from Brazil made by De Andrade Vieira et al found that the total energy in AD patients was 1715.3±492.3 kcal [ 21 ]. Medeiros et al also reported a total energy consumption of 1238.44 kcal among AD patients living in home health care centers [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, De Andrade Vieira et al reported an adequacy percentage of macronutrients (carbohydrates (55.9%) and fats (52.4%)) but a higher protein (17.2%) consumption. In relation to micronutrients, vitamin C intake was acceptable but sodium did not reach the recommended dietary intakes [ 21 ] ( Tables 1 and 2 ). No group achieved the recommend fiber intake.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation